A gas diffusion layer with a multi-gradient structure, a preparation method and application thereof

CN122930948APending Publication Date: 2026-10-16SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611416182.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

(1)均质导电结构使催化层界面易出现局部电流聚集,高电流密度工况下极化损耗显著增大,限制电池峰值功率提升;

Benefits of technology

(1)本发明提出的具有多重梯度结构的气体扩散层,可在保证电子快速传导的同时,均匀分散催化层界面的电流密度,有效缓解传统均质GDL结构中局部电流集中的问题,从而显著降低大电流密度工况下的电化学极化损耗,提升燃料电池的峰值功率密度与输出效率。同时,通过梯度引入惰性导电陶瓷颗粒,GDL的电化学稳定性得到提升,碳基组分在极端工况下的氧化腐蚀得到抑制,从而增强了气体扩散层的结构稳定性与长循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930948A_ABST
    Figure CN122930948A_ABST
Patent Text Reader

Abstract

The application discloses a kind of gas diffusion layer with multiple gradient structure and its preparation method and application, belong to proton exchange membrane fuel cell technical field.The gas diffusion layer is by substrate and is successively arranged on the conductive bottom layer, transition layer and hydrophobic layer;Hydrophobic layer and transition layer are by carbon-based conductive material, inert conductive ceramic particles and polytetrafluoroethylene, and the conductive bottom layer is by carbon-based conductive material and polytetrafluoroethylene;Wherein, the proportion of inert conductive ceramic particles in hydrophobic layer is higher than transition layer, and the content of polytetrafluoroethylene is gradient distribution of hydrophobic layer>transition layer>conductive bottom layer.The structure gives consideration to electron conduction, current distribution and corrosion resistance, and its preparation adopts layered silk screen printing combined with layer-by-layer semi-cured setting and high-temperature sintering process, can be adapted to constant load or variable working condition scene, improves fuel cell output performance and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of proton exchange membrane fuel cell technology, specifically to a gas diffusion layer with a multi-gradient structure, its preparation method, and its application. Background Technology

[0002] Proton exchange membrane fuel cells (PEMFCs), as clean and efficient new energy power devices, possess outstanding advantages such as high energy conversion efficiency, zero pollution emissions, rapid low-temperature start-up, and low operating noise. They are widely used in new energy vehicle power, distributed energy storage, and emergency backup power, and are core key equipment for the industrialization of hydrogen energy. The gas diffusion layer (GDL), as the core porous functional layer of the membrane electrode assembly, undertakes four core functions: electron conduction, reactant gas transport, liquid water drainage, and electrode structure support. Its conductivity, pore structure, and hydrophobicity directly determine the ohmic loss, mass transfer efficiency, output power, and long-term cycle stability of the fuel cell, making it a key material restricting the high-power, long-life operation of fuel cells.

[0003] Traditional homogeneous GDLs exhibit disordered vertical thickness electron transport paths, leading to severe electron congestion under high current conditions, resulting in high bulk resistance, high interfacial contact resistance, and high ohmic losses. Furthermore, single-gradient modified GDLs fail to construct a continuous and controllable conductivity gradient, making it impossible to achieve uniform interfacial current while ensuring low vertical transport resistance. Consequently, it is difficult to achieve a comprehensive performance that balances high conductivity, high mass transfer, and high corrosion resistance.

[0004] Current commercial and laboratory gas diffusion layers all employ a homogeneous conductive design, with the carbon substrate and modified coating exhibiting consistent overall conductivity. However, optimizing mass transfer performance solely through hydrophobic modification or pore size control presents inherent technical limitations. (1) The homogeneous conductive structure makes it easy for local current to accumulate at the catalyst layer interface, and the polarization loss increases significantly under high current density conditions, which limits the improvement of battery peak power. (2) In actual working conditions such as high potential start-up and shutdown, dry and wet alternation, and load fluctuation, the surface carbon material is directly exposed to a strong polarization environment. The carbon oxidation corrosion rate in the current concentration area accelerates sharply, and hydrophobic coating peeling and carbon matrix damage and perforation are likely to occur, resulting in electrode water flooding and performance cliff-like degradation. (3) Traditional structures cannot solve the problems of bulk resistance and corrosion resistance at the same time. Improving the overall conductivity will aggravate the surface electrochemical corrosion, while reducing the overall conductivity will increase the current collection loss. There is a long-standing technical contradiction of performance balance. Summary of the Invention

[0005] This invention addresses the shortcomings of existing technologies by providing a gas diffusion layer with a multi-gradient structure, achieving multi-dimensional technological breakthroughs in rapid electron collection, uniform current distribution, efficient gas-liquid mass transfer, and long-term corrosion resistance, thus meeting the practical application requirements of fuel cells for high power, long life, and variable operating conditions.

[0006] A first aspect of the present invention provides a gas diffusion layer having a multi-gradient structure, characterized in that it comprises a substrate layer and a multi-gradient structure layer disposed on the substrate layer; The multi-gradient structure layer is composed of a conductive bottom layer, a transition layer and a hydrophobic layer in sequence along the direction away from the base layer; The hydrophobic layer is composed of a first carbon-based conductive material, first inert conductive ceramic particles, and polytetrafluoroethylene. The transition layer is composed of a second carbon-based conductive material, second inert conductive ceramic particles, and polytetrafluoroethylene. The conductive substrate is composed of a third carbon-based conductive material and polytetrafluoroethylene; Furthermore, the mass percentage of the first inert conductive ceramic particles in the total mass of the first carbon-based conductive material and the first inert conductive ceramic particles in the hydrophobic layer is higher than the mass percentage of the second inert conductive ceramic particles in the total mass of the second carbon-based conductive material and the second inert conductive ceramic particles in the transition layer; the mass percentage of polytetrafluoroethylene in the hydrophobic layer is higher than the mass percentage of polytetrafluoroethylene in the transition layer, and the mass percentage of polytetrafluoroethylene in the transition layer is higher than the mass percentage of polytetrafluoroethylene in the conductive substrate.

[0007] Furthermore, the first carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the second carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the third carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the first inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide; and the second inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide.

[0008] Furthermore, in the hydrophobic layer, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles is 1:3 to 1:7; in the transition layer, the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles is 1:1 to 1:5.

[0009] Furthermore, the mass percentage of polytetrafluoroethylene in the hydrophobic layer is 14% to 18%, the mass percentage of polytetrafluoroethylene in the transition layer is 8% to 12%, and the mass percentage of polytetrafluoroethylene in the conductive underlayer is 5% to 8%.

[0010] Furthermore, the thickness of the conductive bottom layer is 10μm~20μm, the thickness of the transition layer is 20μm~40μm, and the thickness of the hydrophobic layer is 10μm~20μm.

[0011] A second aspect of the present invention provides a method for preparing the gas diffusion layer having a multi-gradient structure as described above, comprising the following steps: Substrate pretreatment: The carbon paper is cleaned and annealed; Preparation of gradient slurries: The first carbon-based conductive material, the first inert conductive ceramic particles, the first dispersant, and the polytetrafluoroethylene emulsion are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a hydrophobic layer slurry; the second carbon-based conductive material, the second inert conductive ceramic particles, the polytetrafluoroethylene emulsion, and the second dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a transition layer slurry; the third carbon-based conductive material, the polytetrafluoroethylene emulsion, and the third dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a conductive bottom layer slurry; Printing and setting: On the pretreated base layer, the conductive bottom layer paste, the transition layer paste, and the hydrophobic layer paste are sequentially screen printed; after each layer of paste is printed, a setting process is performed to form a semi-cured state; Sintering treatment: The printed and shaped sample is placed in an inert atmosphere and sintered at high temperature to obtain the gas diffusion layer with a multi-gradient structure.

[0012] Furthermore, at least one of the following conditions must be met: The substrate pretreatment includes: ultrasonically cleaning the carbon paper sequentially with acetone, anhydrous ethanol, and deionized water for 10 min to 30 min, drying it at 70℃ to 90℃ for 10 min to 30 min, and then annealing it at 320℃ to 360℃ for 20 min to 40 min in an inert atmosphere. The preparation of the gradient slurry includes: the low-speed stirring time is 10 min to 30 min, and the ultrasonic dispersion time is 20 min to 40 min; The printing and setting process includes setting temperature of 70℃~100℃ and setting time of 5min~15min; The sintering process includes: a sintering temperature of 320℃~350℃ and a sintering time of 30min~60min.

[0013] Further, the preparation of the gradient slurry includes: The first dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; The second dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; The third dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone.

[0014] A third aspect of the present invention provides the application of the gas diffusion layer with a multi-gradient structure described above in a proton exchange membrane fuel cell.

[0015] Furthermore, when used in stationary energy storage constant load scenarios, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:3.5 to 1:4.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.3 to 1:1.7.

[0016] Furthermore, when used in vehicle-mounted variable operating condition scenarios, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:5.5 to 1:6.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.8 to 1:2.2.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The gas diffusion layer with a multi-gradient structure proposed in this invention can uniformly disperse the current density at the catalyst layer interface while ensuring rapid electron conduction, effectively alleviating the problem of local current concentration in the traditional homogeneous GDL structure, thereby significantly reducing electrochemical polarization loss under high current density conditions and improving the peak power density and output efficiency of the fuel cell. At the same time, by introducing inert conductive ceramic particles in a gradient, the electrochemical stability of the GDL is improved, and the oxidation corrosion of the carbon-based components under extreme conditions is suppressed, thereby enhancing the structural stability and long cycle life of the gas diffusion layer.

[0018] (2) The present invention precisely matches the conductivity gradient, porosity gradient and hydrophobic gradient. The conductive bottom layer adopts a large pore design, which has both high air permeability and high conductivity, and can realize the rapid transport of reaction gas and timely discharge of liquid water; the hydrophobic layer adopts a small pore structure, which has high hydrophobicity and uniform conductivity, which is conducive to the uniformity of gas-liquid distribution and tight adhesion with the catalyst layer interface, thereby effectively solving the performance degradation problem caused by water flooding and uneven mass transfer under high power conditions.

[0019] (3) This invention applies the “layered screen printing + low temperature semi-curing” process to the preparation of gradient gas diffusion layer. By relying on the layer-by-layer curing mechanism, the single-layer structure is pre-shaped and there is no cross-contamination between layers. From the source of the process, it ensures that the components of the three-layer coating change independently and gradually, the performance gradient transitions smoothly and there is no interface mutation. This breaks through the technical bottleneck that the traditional molding process cannot accurately control the component gradient. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in the embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings.

[0021] Figure 1 This is a comparison diagram of the contact angles on the microporous layer side between Embodiments 1-2 and the comparative example of the present invention.

[0022] Figure 2 This is a comparison diagram of the porosity of Embodiments 1-2 and the comparative example of the present invention.

[0023] Figure 3 This is a comparison chart of the corrosion current density of Examples 1-2 and the comparative example of the present invention over 10 hours.

[0024] Figure 4 The graph shows a comparison of the polarization curve (a) and power density curve (b) of Embodiments 1-2 and the comparative example of the present invention. Detailed Implementation

[0025] To better understand the above technical solutions, the technical solutions of the embodiments of this application will be described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the embodiments of this application and the specific features in the embodiments are detailed descriptions of the technical solutions of the embodiments of this application, rather than limitations on the technical solutions of this application. In the absence of conflict, the embodiments of this application and the technical features in the embodiments can be combined with each other.

[0026] A first aspect of the present invention provides a gas diffusion layer having a multi-gradient structure, characterized in that it is composed of a substrate layer and a multi-gradient structure layer disposed on the substrate layer; The multi-gradient structure consists of a conductive bottom layer, a transition layer, and a hydrophobic layer in sequence along the direction away from the substrate layer; The hydrophobic layer is composed of a first carbon-based conductive material, first inert conductive ceramic particles, and polytetrafluoroethylene; The transition layer is composed of a second carbon-based conductive material, second inert conductive ceramic particles, and polytetrafluoroethylene; The conductive substrate is composed of a third carbon-based conductive material and polytetrafluoroethylene; Furthermore, the mass percentage of the first inert conductive ceramic particles in the total mass of the first carbon-based conductive material and the first inert conductive ceramic particles in the hydrophobic layer is higher than the mass percentage of the second inert conductive ceramic particles in the total mass of the second carbon-based conductive material and the second inert conductive ceramic particles in the transition layer; the mass percentage of polytetrafluoroethylene in the hydrophobic layer is higher than the mass percentage of polytetrafluoroethylene in the transition layer, and the mass percentage of polytetrafluoroethylene in the transition layer is higher than the mass percentage of polytetrafluoroethylene in the conductive substrate.

[0027] This invention innovatively proposes a fuel cell gas diffusion layer with a multi-gradient structure. By constructing a triple synergistic gradient structure (porosity, hydrophobicity, and conductivity), it achieves multi-dimensional technological breakthroughs in rapid electron current collection, uniform current distribution, efficient gas-liquid mass transfer, and long-term corrosion resistance. It overcomes the shortcomings of existing technologies, such as uneven current distribution in homogeneous conductive gas diffusion layers, severe local electrochemical corrosion, poor stability under high current conditions, inability to balance conductivity and corrosion resistance, and rapid degradation over long cycles. This invention is suitable for the practical application requirements of fuel cells for high power, long life, and variable operating conditions.

[0028] The conductive bottom layer is dominated by a third carbon-based conductive material, which can ensure excellent conductivity and current collection performance. The transition layer is composed of a second carbon-based conductive material, a second inert conductive ceramic particle, and polytetrafluoroethylene. Along the direction away from the base layer, the mass ratio of inert conductive ceramic particles gradually increases, achieving a smooth transition of conductivity without interface abrupt changes. The hydrophobic layer is composed of a first inert conductive ceramic particle, a first carbon-based conductive material, and polytetrafluoroethylene, resulting in a hydrophobic layer with strong hydrophobicity and high corrosion resistance.

[0029] In some embodiments, the first carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the second carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the third carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; the first inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide; and the second inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide.

[0030] Optionally, titanium carbide (TiC) is provided by Suzhou Keyue New Materials, with a particle size range of 0.5μm to 5μm. The present invention preferably uses TiC with a particle size of 1μm to 1.2μm, because excessively large particle size will clog the mesh, and excessively high nanoscale specific surface area will cause the slurry viscosity to rise sharply, which is not conducive to screen printing. Its melting point is 3140℃ to 3160℃, and it is completely stable when sintered at 320℃ to 350℃ in an inert atmosphere without melting or phase transformation. It is also insoluble in water, dilute acid and alkali at room temperature, and is only corroded by a mixture of concentrated nitric acid and hydrofluoric acid. Zirconium carbide (ZrC) is supplied by Liaoning Jiamai New Materials, with a particle size range of 0.8μm to 10μm. The preferred ZrC particle size in this invention is 1μm to 1.2μm. It has a melting point of 3530℃ to 3540℃, is completely stable when sintered at 320℃ to 350℃ in an inert atmosphere, is insoluble in water and dilute hydrochloric acid at room temperature, has better acid resistance than TiC, and is only soluble in a hot concentrated nitric acid-hydrofluoric acid mixture.

[0031] In some embodiments, in the hydrophobic layer, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles is 1:3 to 1:7; in the transition layer, the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles is 1:1 to 1:5.

[0032] Specifically, for the transition layer, when the mass ratio of ceramic to carbon is less than 1:1, the ceramic particles do not adequately coat the carbon matrix, making it difficult to achieve a smooth transition of components to the hydrophobic layer. This can easily cause abrupt changes in interlayer composition, leading to interfacial stress and the risk of coating delamination. If the ratio is greater than 5:1, the carbon skeleton is fragmented by the ceramic particles, resulting in increased contact resistance and decreased porosity. For the hydrophobic layer, if the mass ratio of ceramic to carbon is less than 3:1, the ceramic particles are insufficient to fully coat the carbon matrix, increasing the risk of carbon oxidation and corrosion at high potentials and failing to homogenize the catalytic layer interfacial current. If the ratio is greater than 7:1, the conductive pathway is broken, ohmic polarization deteriorates, and the ceramic particles and polytetrafluoroethylene fill the micropores, making them prone to flooding under high power.

[0033] In some embodiments, the mass percentage of polytetrafluoroethylene (PTFE) in the hydrophobic layer is 14% to 18%, the mass percentage of PTFE in the transition layer is 8% to 12%, and the mass percentage of PTFE in the conductive underlayer is 5% to 8%.

[0034] Specifically, the mass percentage of polytetrafluoroethylene (PTFE) in the conductive underlayer, transition layer, and hydrophobic layer is controlled at 5%~8%, 8%~12%, and 14%~18%, respectively, showing a progressively increasing distribution and synergistically cooperating with the carbon-based conductive material-inert conductive ceramic particle composition gradient. The PTFE in the conductive underlayer primarily functions as a binder, preventing coating detachment; however, excessive PTFE can reduce conductivity, fill interconnected pores, and increase mass transfer resistance. The PTFE in the transition layer helps enhance interlayer bonding strength and construct a preliminary hydrophobic barrier; however, excessive PTFE can increase resistance and easily cause cross-layer penetration during sintering and melting, disrupting the gradient structure. The PTFE in the hydrophobic layer forms a continuous hydrophobic network to suppress water flooding while firmly bonding the inert conductive ceramic particles, ensuring corrosion resistance; however, excessive PTFE can disrupt conductive pathways, significantly increasing ohmic resistance and worsening gas-liquid mass transfer. Within the aforementioned ranges, the content of each layer achieves a balance between the hydrophobic, bonding, and insulating effects of PTFE while avoiding its adverse effects, thus optimizing overall performance.

[0035] In some embodiments, the thickness of the conductive substrate is 10 μm to 20 μm, the thickness of the transition layer is 20 μm to 40 μm, and the thickness of the hydrophobic layer is 10 μm to 20 μm.

[0036] Specifically, the thicknesses of the conductive substrate, transition layer, and hydrophobic layer are 10μm~20μm, 20μm~40μm, and 10μm~20μm, respectively, exhibiting an overall "thin-thick-thin" configuration. The conductive substrate focuses on current collection, while the hydrophobic layer focuses on corrosion protection and water management; therefore, both are kept relatively thin. The transition layer, as the core buffer layer for achieving a smooth gradient in composition, conductivity, and porosity, is set to be the thickest of the three layers. Optionally, the transition layer is at least 5μm thicker than the conductive substrate and at least 5μm thicker than the hydrophobic layer. If the transition layer is too thin, the composition gradient is compressed, the smooth transition effect is not obvious, and it is easy to cause local contact between the substrate and the hydrophobic layer, resulting in the failure of the stress buffering function. If the transition layer is too thick, its conductivity is lower than that of the conductive substrate, the excessively long vertical electron transport path will increase the volume resistance, and the gas-liquid diffusion path will increase, causing liquid water to stagnate within the layer and exacerbating flooding.

[0037] A second aspect of the present invention provides a method for preparing the gas diffusion layer with a multi-gradient structure described above, comprising the following steps: Substrate pretreatment: The carbon paper is cleaned and annealed; Preparation of gradient slurries: The first carbon-based conductive material, the first inert conductive ceramic particles, the first dispersant, and the polytetrafluoroethylene emulsion are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a hydrophobic layer slurry; the second carbon-based conductive material, the second inert conductive ceramic particles, the polytetrafluoroethylene emulsion, and the second dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a transition layer slurry; the third carbon-based conductive material, the polytetrafluoroethylene emulsion, and the third dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a conductive bottom layer slurry; Printing and setting: Conductive base layer paste, transition layer paste and hydrophobic layer paste are screen printed sequentially on the pretreated base layer; after each layer of paste is printed, a setting process is performed to form a semi-cured state; Sintering treatment: The printed and shaped sample is placed in an inert atmosphere and sintered at high temperature to obtain a gas diffusion layer with a multi-gradient structure.

[0038] In this embodiment of the invention, a "layered screen printing + low-temperature semi-curing" process is used to sequentially coat three different types of pastes with different properties onto the surface of a substrate layer to obtain a gas diffusion layer with a triple synergistic structure of gradient conductivity, porosity, and hydrophobicity. The conductivity gradient is mainly obtained by adjusting the ratio of carbon-based conductive material to inert conductive ceramic particles in the paste layer by layer, so that the conductivity decreases monotonically from the substrate layer to the microporous layer, and further achieves a monotonically decreasing porosity and a monotonically increasing hydrophobicity in the same direction.

[0039] In some embodiments, the substrate pretreatment includes: ultrasonically cleaning the carbon paper sequentially with acetone, anhydrous ethanol, and deionized water for 10 min to 30 min, drying it at 70°C to 90°C for 10 min to 30 min, and then annealing it at 320°C to 360°C for 20 min to 40 min under an inert atmosphere.

[0040] Specifically, the carbon paper is ultrasonically cleaned and dried sequentially with acetone, anhydrous ethanol, and deionized water to remove residual organic impurities from the substrate surface; the conductivity and structural stability of the substrate are improved by annealing in an inert atmosphere to obtain a modified support substrate.

[0041] In some embodiments, the preparation of gradient slurry includes: low-speed stirring for 10 min to 30 min and ultrasonic dispersion for 20 min to 40 min.

[0042] Specifically, in the process of preparing gradient slurry, low-speed stirring is used to achieve preliminary mixing, followed by continuous ultrasonic dispersion to ensure uniform dispersion of the slurry.

[0043] In some embodiments, printing and setting include: setting temperature of 70°C to 100°C and setting time of 5 min to 15 min.

[0044] Specifically, after each layer is printed, it is placed in a vacuum low-temperature drying oven for setting treatment. The setting temperature is 70℃~100℃ and the setting time is 5min~15min. By semi-curing layer by layer, the mixing of the slurry between layers is suppressed, so as to form a gradient system with gradual changes in components and regular structure.

[0045] In some embodiments, the sintering process includes: a sintering temperature of 320°C to 350°C and a sintering time of 30 min to 60 min.

[0046] Specifically, the printed gas diffusion layer sample is placed in an inert atmosphere and sintered at high temperature to solidify each coating structure and pyrolyze the residual dispersant to achieve integrated multi-layer structure, thus obtaining a gas diffusion layer with a multi-gradient structure.

[0047] In some embodiments, the gradient slurry is prepared by: a first dispersant selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; a second dispersant selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; and a third dispersant selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone.

[0048] Optionally, the amount of dispersant added to each layer is 1 wt% of the total mass of the solid phase in that layer, where the total mass of the solid phase is equal to the mass of the carbon-based conductive filler, the mass of the inert conductive ceramic particles, and the mass of the PTFE dry matter.

[0049] A third aspect of the present invention provides the application of the gas diffusion layer with the multi-gradient structure described above in a proton exchange membrane fuel cell.

[0050] In some embodiments, when used in a stationary energy storage constant load scenario, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:3.5 to 1:4.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.3 to 1:1.7.

[0051] In some embodiments, when used in vehicle-mounted variable operating condition scenarios, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:5.5 to 1:6.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.8 to 1:2.2.

[0052] Example 1: A gas diffusion layer with a multi-gradient structure and its preparation method (a) Gas diffusion layer with multi-gradient structure It consists of a substrate layer and a multi-gradient structure layer disposed on the substrate layer. The multi-gradient structure layer consists of a conductive sublayer, a transition layer, and a hydrophobic layer in sequence along the direction away from the substrate layer; wherein... The base layer is pretreated TGP-060 commercial carbon paper; The conductive substrate is composed of carbon nanotubes, conductive graphite powder and polytetrafluoroethylene (PTFE). The PTFE content in the conductive substrate is 6% by mass, and the thickness of the conductive substrate is 15 μm. The transition layer is composed of carbon nanotubes, titanium carbide particles and polytetrafluoroethylene. The titanium carbide particles account for 60% of the total mass of carbon nanotubes and titanium carbide particles in the transition layer, the PTFE mass percentage in the transition layer is 10%, and the thickness of the transition layer is 20 μm. The hydrophobic layer is composed of carbon nanotubes, titanium carbide particles and polytetrafluoroethylene (PTFE). The titanium carbide particles account for 80% of the total mass of carbon nanotubes and titanium carbide particles in the hydrophobic layer, the PTFE mass percentage in the hydrophobic layer is 16%, and the thickness of the hydrophobic layer is 15 μm.

[0053] It should be noted that the PTFE mass percentage in each layer is calculated as follows: PTFE dry matter mass ÷ (carbon-based conductive filler mass + inert conductive ceramic particle mass + PTFE dry matter mass) × 100%.

[0054] (II) Preparation method Includes the following steps: (1) Substrate pretreatment: TGP-060 commercial carbon paper was selected and ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 min each, dried at 80℃, annealed at 350℃ for 30 min under nitrogen atmosphere, and then naturally cooled for use. (2) Slurry preparation: Conductive bottom slurry: 0.8g carbon nanotubes, 1.2g conductive graphite powder, 0.18mL 60% PTFE emulsion (corresponding to 0.13g PTFE dry material), 0.021g PVP dispersant, 20mL anhydrous ethanol, stirred at 100rpm for 10min, and ultrasonically dispersed for 30min; Transition layer slurry: 0.8g carbon nanotubes, 1.2g titanium carbide particles, 0.31mL 60% PTFE emulsion (corresponding to 0.223g PTFE dry material), 0.022g PVP dispersant, 20mL anhydrous ethanol, stirred at 100rpm for 10min, and ultrasonically dispersed for 30min; Hydrophobic layer slurry: 0.4g carbon nanotubes, 1.6g titanium carbide particles, 0.53mL 60% PTFE emulsion (corresponding to 0.382g PTFE dry material), 0.024g PVP dispersant, 20mL anhydrous ethanol, stirred at 100rpm for 10min, and ultrasonically dispersed for 30min; (3) Printing and setting: The paste layers are screen printed in sequence, and the thickness is controlled as follows: conductive bottom layer 15μm, transition layer 20μm, hydrophobic layer 15μm. After each layer is printed, the sample is placed in a vacuum drying oven, the temperature is set at 80℃ and the duration is 10min, and the setting process is carried out. (4) High-temperature sintering: Sinter at 330℃ for 50 min under nitrogen atmosphere, cool naturally and cut to obtain the finished gradient conductive gas diffusion layer.

[0055] Example 2 (a) Gas diffusion layer with multi-gradient structure It consists of a substrate layer and a multi-gradient structure layer disposed on the substrate layer. The multi-gradient structure layer consists of a conductive sublayer, a transition layer, and a hydrophobic layer sequentially along the direction away from the substrate layer; wherein... The base layer is pretreated TGP-060 commercial carbon paper; The conductive substrate is composed of carbon nanotubes, conductive graphite powder and polytetrafluoroethylene (PTFE). The PTFE content in the conductive substrate is 6% by mass, and the thickness of the conductive substrate is 15 μm. The transition layer is composed of carbon nanotubes, titanium carbide particles and polytetrafluoroethylene. The titanium carbide particles account for 66.5% of the total mass of carbon nanotubes and titanium carbide particles in the transition layer, the PTFE mass percentage in the transition layer is 10%, and the thickness of the transition layer is 20 μm. The hydrophobic layer is composed of carbon nanotubes, titanium carbide particles and polytetrafluoroethylene (PTFE). The titanium carbide particles account for 85% of the total mass of carbon nanotubes and titanium carbide particles in the hydrophobic layer, the PTFE mass percentage in the hydrophobic layer is 16%, and the thickness of the hydrophobic layer is 15 μm.

[0056] (II) Preparation method The difference between Example 2 and Example 1 lies in the adjustment of the ratio of carbon nanotubes to titanium carbide in the transition layer and hydrophobic layer slurry. The specific slurry preparation is as follows: Conductive underlayer paste: Same as in Example 1; Transition layer slurry: 0.67g carbon nanotubes, 1.33g titanium carbide particles, 0.31mL 60% PTFE emulsion, 0.022g PVP dispersant, 20mL anhydrous ethanol, stirred at 100rpm for 10min, and ultrasonically dispersed for 30min; Hydrophobic slurry: 0.3g carbon nanotubes, 1.7g titanium carbide particles, 0.53mL 60% PTFE emulsion, 0.025g PVP dispersant, 20mL anhydrous ethanol, stirred at 100rpm for 10min, and ultrasonically dispersed for 30min.

[0057] The remaining preparation steps are exactly the same as in Example 1.

[0058] Comparative Example (a) Homogeneous gas diffusion layer It consists of a pretreated TGP-060 commercial carbon paper as the base layer and a microporous layer disposed thereon. The microporous layer is a homogeneous coating containing only carbon-based conductive materials and PTFE, without adding inert conductive ceramic particles; there is no gradient change along the thickness direction, the carbon-based conductive materials and PTFE are uniformly distributed, and the thickness of the microporous layer is 50μm.

[0059] (II) Preparation method Includes the following steps: (1) Substrate pretreatment: Same as in Example 1.

[0060] (2) Slurry preparation: Take 8g of conductive carbon black, 2.78mL of 60% PTFE emulsion (corresponding to 2.00g of dry PTFE), 0.10g of PVP dispersant and 50.7mL of anhydrous ethanol. Add the conductive carbon black and PVP dispersant to the beaker in sequence, add anhydrous ethanol, and then add the PTFE emulsion. Stir at low speed of 100rpm for 20min to complete the pre-dispersion. Then, ultrasonically disperse for 30min to avoid PTFE emulsion demulsification and agglomeration. After ultrasonication, shake the slurry evenly and stir at low speed for 5min again before coating to inhibit carbon black sedimentation, so as to obtain a microporous layer slurry with completely uniform components.

[0061] (3) Printing and setting: The coating was applied by screen printing, and the thickness of the microporous layer was controlled to be 50 μm. After printing, the sample was placed in a vacuum drying oven and dried at 80°C for 10 min for setting.

[0062] (4) High-temperature sintering: Same as in Example 1.

[0063] To further compare the differences in physical properties and electrochemical properties between the gas diffusion layer with a multi-gradient structure in Examples 1-2 and the homogeneous gas diffusion layer in the comparative example, contact angle, monolayer conductivity, and porosity tests were performed to verify the gas-liquid transport and electron conduction capabilities of the gas diffusion layer with a multi-gradient structure. Subsequently, offline accelerated corrosion tests were conducted on it in a conventional three-electrode system. During the process, a constant potential of 1.5V and a water bath environment of 80°C were applied using an electrochemical workstation. After 36,000 s (10 h), the stability of the gas diffusion layer with a multi-gradient structure in the simulated PEMFC environment was evaluated based on the change in corrosion current density. Finally, the gas diffusion layer with a multi-gradient structure and the homogeneous gas diffusion layer were used as cathode diffusion layers to assemble a single cell, and polarization curves and power density tests were performed on it.

[0064] To further compare the differences in physical properties and electrochemical performance between the gas diffusion layer with a multi-gradient structure in Examples 1-2 and the homogeneous gas diffusion layer in the comparative example, contact angle, monolayer conductivity, and porosity tests were conducted to evaluate their capabilities in gas-liquid transport and electron conduction. Subsequently, offline accelerated corrosion tests were performed in a conventional three-electrode system. During the tests, a constant potential of 1.5V was applied using an electrochemical workstation, and the system was run for 10 hours in an 80°C water bath. The stability of the gas diffusion layer with a multi-gradient structure in the simulated PEMFC operating environment was evaluated based on the change in corrosion current density. Finally, the gas diffusion layer with a multi-gradient structure and the homogeneous gas diffusion layer were used as cathode diffusion layers to assemble single cells, and polarization curves and power density tests were performed.

[0065] Results Analysis Depend on Figure 1 It can be seen that the surface water contact angles of Examples 1 and 2 of the present invention reach 150° and 148° respectively, both significantly higher than the 141° of the comparative example. Under the high current density operation of the fuel cell, the catalyst layer reacts to generate a large amount of liquid water. The highly hydrophobic surface can effectively suppress the retention of liquid water in the pores, reduce the probability of the pores being blocked by liquid water, alleviate flooding, reduce concentration polarization, and help improve the output performance and operational stability of the battery.

[0066] Figure 2 In Examples 1 and 2, the total porosity was 84.8% and 82.5%, respectively, significantly higher than the 73.7% of the comparative example. The higher interconnected porosity creates a more efficient dual-channel transport system for the reactant gas and liquid water: on the one hand, the oxidant gas can smoothly reach the catalytic reaction interface, ensuring reactant supply; on the other hand, the liquid water generated in the catalytic layer can be quickly discharged through the interconnected channels, reducing mass transfer resistance. Importantly, high porosity needs to be combined with good hydrophobicity to achieve optimal results. Therefore, this invention simultaneously achieves high total porosity and hydrophobicity, optimizing gas-liquid transport performance concurrently.

[0067] The results of the layered conductivity tests (Table 1) show that both Examples 1 and 2 exhibit a vertical gradient of "high conductivity in the conductive bottom layer, medium conductivity in the transition layer, and low conductivity in the hydrophobic layer." Specifically, the conductive bottom layer has the highest conductivity, reaching 305 S / cm and 303 S / cm in Examples 1 and 2, respectively. Being close to the carbon paper substrate, it is dominated by carbon-based conductive materials with a low proportion of polytetrafluoroethylene (PTFE), ensuring efficient electron transport and reducing ohmic polarization. The transition layer has a moderate conductivity, at 232 S / cm in Examples 1 and 234 S / cm in Examples 2. In this layer, the proportion of carbon-based conductive filler decreases while the proportion of inert conductive ceramic particles increases, and the PTFE content increases simultaneously, resulting in a moderate decrease in conductivity. This layer serves as a smooth transition between components and electrical properties, avoiding the introduction of additional interfacial contact resistance due to abrupt performance changes. The hydrophobic layer has the lowest conductivity, at 145 S / cm in Example 1 and 128 S / cm in Example 2. This layer directly faces the catalyst layer, and its content of inert conductive ceramic particles and polytetrafluoroethylene is the highest among the three layers. Compared with the gradient structure of this invention, the homogeneous structure in the comparative example (238 S / cm) cannot simultaneously meet the requirements of "substrate conductivity and current collection" and "catalyst layer corrosion protection".

[0068] Table 1. Comparison of monolayer conductivity of the diffusion layer in the embodiments of the present invention and the comparative examples.

[0069] Figure 3 In the comparative GDL sample, without inert particle protection, the carbon material underwent continuous oxidation and corrosion, with the steady-state corrosion current density continuously increasing to 108 μA·cm. - Conversely, the inert conductive particles in the hydrophobic layer of the samples in Examples 1 and 2 can effectively coat the carbon matrix and isolate the corrosive environment, resulting in a significant reduction in corrosion current density. Among them, due to the higher titanium carbide doping content in Example 2, its steady-state corrosion current density is the lowest, which can withstand harsh conditions such as frequent start-stop and high-potential oxidation, and has better long-term cycle stability.

[0070] Depend on Figure 4 The single-cell polarization curves of sample a show that, across the entire current density range, the overall performance of the single cell follows the pattern: Example 1 > Example 2 > Comparative Example. Specifically, in the low current density range, the performance of the three groups of samples is similar; when the current density exceeds 0.6 A·cm⁻¹... -2 Subsequently, the structural advantages of the gradient GDL of the present invention gradually become apparent, specifically manifested in the 1.5 A·cm -2 Under operating conditions, the output voltage of Example 1 can reach 0.6V, significantly higher than the 0.51V of the comparative example. Figure 4 As can be seen from the power density curve of b, compared to the comparative example (peak power density 0.84 W·cm²), -2The peak power density of Examples 1 and 2 was increased by 13.1% and 3.6%, respectively.

[0071] It should be noted that Examples 1 and 2 in this invention represent two typical preferred formulations, each with its own emphasis, and neither is inherently superior or inferior. Example 1 has a higher proportion of carbon-based conductive filler in the hydrophobic layer, resulting in higher overall conductivity, total porosity, and hydrophobic angle for the GDL. This leads to a higher peak power density after assembling a single cell, making it more suitable for stationary energy storage fuel cell scenarios with stable constant-load operation. Example 2 further increases the proportion of inert conductive titanium carbide particles in the hydrophobic layer. While this reduces some conductivity and mass transfer performance, it achieves superior corrosion resistance, enabling it to withstand harsh conditions such as frequent start-stop cycles and high-potential oxidation. It also exhibits better long-cycle stability, making it more suitable for the variable operating conditions of on-board proton exchange membrane fuel cells.

[0072] In summary, the GDL with a multi-gradient structure prepared by this invention significantly improves the power density and stability of fuel cells, and has good prospects for engineering applications.

[0073] It will be readily understood by those skilled in the art that the above-described advantageous methods can be freely combined and superimposed without conflict. The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application. The above are merely preferred embodiments of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of this application, and these improvements and modifications should also be considered within the protection scope of this application.

Claims

1. A gas diffusion layer with a multi-gradient structure, characterized in that, It consists of a base layer and a multi-gradient structure layer disposed on the base layer; The multi-gradient structure layer is composed of a conductive bottom layer, a transition layer and a hydrophobic layer in sequence along the direction away from the base layer; The hydrophobic layer is composed of a first carbon-based conductive material, first inert conductive ceramic particles, and polytetrafluoroethylene. The transition layer is composed of a second carbon-based conductive material, second inert conductive ceramic particles, and polytetrafluoroethylene. The conductive substrate is composed of a third carbon-based conductive material and polytetrafluoroethylene; Furthermore, the mass percentage of the first inert conductive ceramic particles in the total mass of the first carbon-based conductive material and the first inert conductive ceramic particles in the hydrophobic layer is higher than the mass percentage of the second inert conductive ceramic particles in the total mass of the second carbon-based conductive material and the second inert conductive ceramic particles in the transition layer; the mass percentage of polytetrafluoroethylene in the hydrophobic layer is higher than the mass percentage of polytetrafluoroethylene in the transition layer, and the mass percentage of polytetrafluoroethylene in the transition layer is higher than the mass percentage of polytetrafluoroethylene in the conductive substrate.

2. The gas diffusion layer according to claim 1, characterized in that, The first carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; The second carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder; The third carbon-based conductive material is selected from at least one of carbon nanotubes and conductive graphite powder. The first inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide; The second inert conductive ceramic particles are selected from at least one of titanium carbide and zirconium carbide.

3. The gas diffusion layer according to claim 1, characterized in that, In the hydrophobic layer, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles is 1:3 to 1:

7. In the transition layer, the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles is 1:1 to 1:

5.

4. The gas diffusion layer according to claim 1, characterized in that, The mass percentage of polytetrafluoroethylene (PTFE) in the hydrophobic layer is 14% to 18%, the mass percentage of PTFE in the transition layer is 8% to 12%, and the mass percentage of PTFE in the conductive underlayer is 5% to 8%.

5. The gas diffusion layer according to any one of claims 1-4, characterized in that, The conductive substrate has a thickness of 10μm to 20μm, the transition layer has a thickness of 20μm to 40μm, and the hydrophobic layer has a thickness of 10μm to 20μm.

6. A method for preparing a gas diffusion layer with a multi-gradient structure as described in any one of claims 1-5, characterized in that, Includes the following steps: Substrate pretreatment: The carbon paper is cleaned and annealed; Preparation of gradient slurries: The first carbon-based conductive material, the first inert conductive ceramic particles, polytetrafluoroethylene emulsion, and the first dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a hydrophobic layer slurry; The second carbon-based conductive material, the second inert conductive ceramic particles, polytetrafluoroethylene emulsion, and the second dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a transition layer slurry; The third carbon-based conductive material, polytetrafluoroethylene emulsion, and the third dispersant are added to anhydrous ethanol, pre-mixed by low-speed stirring, and then ultrasonically dispersed to obtain a conductive bottom layer slurry; Printing and setting: On the pretreated base layer, the conductive bottom layer paste, the transition layer paste, and the hydrophobic layer paste are sequentially screen printed; after each layer of paste is printed, a setting process is performed to form a semi-cured state; Sintering treatment: The printed and shaped sample is placed in an inert atmosphere and sintered at high temperature to obtain the gas diffusion layer with a multi-gradient structure.

7. The preparation method according to claim 6, characterized in that, At least one of the following conditions must be met: The substrate pretreatment includes: ultrasonically cleaning the carbon paper sequentially with acetone, anhydrous ethanol, and deionized water for 10 min to 30 min, drying it at 70℃ to 90℃ for 10 min to 30 min, and then annealing it at 320℃ to 360℃ for 20 min to 40 min in an inert atmosphere. The preparation of the gradient slurry includes: the low-speed stirring time is 10 min to 30 min, and the ultrasonic dispersion time is 20 min to 40 min; The printing and setting process includes setting temperature of 70℃~100℃ and setting time of 5min~15min; The sintering process includes: a sintering temperature of 320℃~350℃ and a sintering time of 30min~60min.

8. The preparation method according to claim 6, characterized in that, The preparation of the gradient slurry includes: The first dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; The second dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone; The third dispersant is selected from at least one of polyvinylpyrrolidone and N-methylpyrrolidone.

9. The application of a gas diffusion layer with a multi-gradient structure as described in any one of claims 1-5 in a proton exchange membrane fuel cell.

10. The application according to claim 9, characterized in that, When used in stationary energy storage constant load scenarios, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:3.5 to 1:4.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.3 to 1:1.

7. When used in vehicle-mounted variable operating conditions, the mass ratio of the first carbon-based conductive material to the first inert conductive ceramic particles in the hydrophobic layer is 1:5.5 to 1:6.5, and the mass ratio of the second carbon-based conductive material to the second inert conductive ceramic particles in the transition layer is 1:1.8 to 1:2.2.